Language Attitudes of Foreigners Residing in Lithuania towards the Lithuanian Language: Insights from a Qualitative Study - Ramonaitė, Jogilė Teresa (Vilnius University Open Series, 2023)
This paper presents a qualitative study investigating the language attitudes of foreign residents living in Lithuania. Through in-depth interviews with individuals of diverse backgrounds who have migrated to Lithuania at different times, the article explores their language-related experiences in the country and their perspectives on the Lithuanian language. The study analyzes these attitudes from a triadic model perspective, encompassing cognitive, affective, and behavioral dimensions. The participants vary in their level of proficiency in Lithuanian and thus their reflections help to reveal the connection between behavioral efforts to learn and use the language and the other dimensions. The study presented elaborates on the comprehended necessity (or lack thereof) to know Lithuanian when living in Lithuania, the emotional comfortability when knowing the language, the effect of the perceived attitudes of Lithuanians towards foreigners who do and who do not know the language, the character of the Lithuanian people reflected in the language, and putting effort to learn the language as a sign of respect towards the host country. While the cognitive dimension is more readily articulated, it alone is insufficient, and a more significant shift is possible when there is a breakthrough in the affective dimension. Even though the data for this study was collected before Lithuania became more economically attractive to foreign immigrants, the results are especially pertinent in the current situation with more economic migrants and war refugees coming to live in the country. Although it is possible to live in Lithuania without knowing the language, if it is not required for one’s job, in order to be an integrative part of the society the foreigner starts to feel not only the necessity but also a desire to know the language.
Keywords: Lithuanian L2; language attitudes; cognitive component; affective component; foreigners in Lithuania